Revealing novel insights into the improvement of greenhouse tea quality through exogenous substance interventions using targeted and untargeted metabolomics and microbial community analyses - Haozhen Li; Shuyao Wang; Xiaohua Zhang; Kangkang Song; Long Yang (Food Chemistry: X)
Tea quality in greenhouse was certain gap with open air. Metabolites and foliar microorganisms were investigated under seaweed fertiliser (CF) and gibberellin (CH) treatments using sensory evaluation, HPLC, untargeted metabolomics, 16S rDNA, and Internal Transcribed Spacer. CF tea was mellow, less astringent, and of better quality compared to CH. Catechin, −(−)Epicatechin, and Epigallocatechin were notably lower in CF. Differentially accumulated metabolites (DAMs) were notably enriched in Flavonoid and Phenylpropanoid biosynthesis, both involved in Catechin synthesis. DAMs in these pathways appeared down-regulated in CF. The CF improved quality by down-regulating metabolites in Phenylpropanoid biosynthesis in conjunction with microbial community metabolism enriched in amino acid and secondary metabolite biosynthesis. Metabolite- microbial correlation analysis indicated that the highest correlation with phenylpropane pathway metabolites was in bacteria Variovorax and Pseudomonas, and in fungi Filobasidium. The study provides theoretical basis for regulating flavour quality of greenhouse tea.